2019
DOI: 10.1007/s10649-019-09892-9
|View full text |Cite
|
Sign up to set email alerts
|

Students’ collaborative decision-making processes in defining and classifying quadrilaterals: a semiotic/dialogic approach

Abstract: In this paper, we take a semiotic/dialogic approach to investigate how a group of UK 12-13year-old students work with hierarchical defining and classifying quadrilaterals. Through qualitatively analysing students' decision-making processes, we found that the students' decision-making processes are interpreted as transforming their informal/personal semiotic representations of Bparallelogram^(object) to more institutional ones. We also found that students' decision-making was influenced by their inability to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Working with others requires the ability to resolve conflicts, use effective communication strategies, manage time and tasks (Beccaria et al, 2014). Fujita, Doney and Wegerif (2019) recently indicated in a specific case of mathematics that students' decision-making was influenced by their inability to see their peers' points of view dialogically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working with others requires the ability to resolve conflicts, use effective communication strategies, manage time and tasks (Beccaria et al, 2014). Fujita, Doney and Wegerif (2019) recently indicated in a specific case of mathematics that students' decision-making was influenced by their inability to see their peers' points of view dialogically.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen (2006) found that students evaluate the group experience as positive if certain conditions are met (Eunjung, 2011, Martin et al, 2019. Fujita, Doney and Wegerif (2019) indicated in the specific case of collaboration in mathematics that students' decision-making was influenced by their inability to see their peers' points of view dialogically. LaBeouf et al (2016) examined faculty and students' comments of a university to determine perceptions of group work.…”
Section: Introductionmentioning
confidence: 99%
“…Kemudian penelitian pada segiempat cenderung berfokus pada pemecahan masalah dan kesulitan siswa dalam menyelesaikan masalah segiempat (Fujita, 2012;Fujita, Doney, & Wegerif, 2019). Sehingga penelitian tentang PCK guru dalam mengajarkan segiempat yang ditinjau dari segi gender perlu dilakukan guna mendapatkan gambaran lebih rinci terkait PCK guru matematika.…”
unclassified
“…The second line of design promotes collaboration among students in order to encourage the production of conjectures and arguments that might not appear without discussion with others. Indeed, through collaborating, students can exchange different representations of geometric objects and negotiate with one another to reach collective definitions of particular geometric objects (Fujita et al, 2019). Following these two design lines, the research project envisages the design of three working areas, which have different didactical functionalities, i.e.…”
Section: The Design Of the Digital Environmentmentioning
confidence: 99%
“…Students should be able to share and justify the processes and procedures used, providing adequate arguments to support or refute mathematical statements (NCTM, 2000).When students produce arguments, they elaborate and explain to themselves the concepts they are justifying (Baker, 2003) and this process can help them to integrate new information within existing cognitive structures (Chi et al, 1989). However, a collaborative approach based on the social and individual construction of knowledge (Vygotsky, 1980), encouraging the engagement of students, could promote the development of argumentative and communicative skills (Leitão, 2000;Andriessen et al, 2003;Lazarou et al, 2016;Albano & Dello Iacono, 2018;Fujita et al, 2019). Students, interacting with peers, on the one hand, can compare their own ideas with those of others and, on the other, can explain and justify their reasoning to try to convince each other of the validity of their arguments.…”
mentioning
confidence: 99%